The Application of Computer Network Technology in Power Information Communication Function. Issue 3 (February 2021) - Cai, Shuo; Cheng, Siyuan; Li, Yichao; Yin, Didi
Abstract: Electric power communication is the key to the formation of advanced, efficient power system elements, is to maintain the normal operation conditions of power market, the premise is to ensure that the computer network security, stability, is to realize the national non-electric industry diversification, the key to enrichment, is the focus of the development of advanced, scientific power management system. In the process of rapid economic development in our country, the society is also in constant development and progress, electric power communication technology is also continuously serving and contributing to the society, and computer network is also constantly expanding in the society. In this paper, the electrical computer network is introduced, and the prospect of electrical computer network is prospected through the power communication technology.